Arrangement of Subunits in 20 S Particles Consisting of NSF, SNAPs, and SNARE Complexes - Hohl, Tobias M. (Mol Cell, 1998)
The structure of 20 S particles, consisting of NSF, SNAPs, and SNARE complexes, was analyzed by electron microscopy and fluorescence resonance energy transfer. Structural changes associated with the binding of α-SNAP and NSF to SNARE complexes define the contribution of each component to the 20 S particle structure. The synaptic SNARE complex forms a 2.5 × 15 nm rod. α-SNAP binds laterally to the rod, increasing its width but not its length. NSF binds to one end of the SNAP/SNARE complex; the resulting 20 S particles measure 22 nm in length and vary in width from 6 nm at their narrowest point to 13.5 nm at their widest. The transmembrane domains of VAMP and syntaxin emerge together at the NSF-distal end of 20 S particles, adjacent to the amino terminus of α-SNAP.